2013
DOI: 10.1002/14651858.cd009688.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for the symptoms and signs resulting from jellyfish stings

Abstract: Analysis 2.3. Comparison 2 Short duration (3-4 days) versus long duration (7-14 days) IV therapy, Outcome 3 Persistent kidney

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 50 publications
3
29
0
Order By: Relevance
“…We strongly concur with the calls by Li and others (Li et al, 2013) for additional pre-clinical and clinical studies to elucidate optimal care after serious jellyfish stings.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…We strongly concur with the calls by Li and others (Li et al, 2013) for additional pre-clinical and clinical studies to elucidate optimal care after serious jellyfish stings.…”
Section: Discussionsupporting
confidence: 83%
“…A recent review published by Li and colleagues in the Cochrane Database of Systemic Reviews, examining 'interventions for the treatment of jellyfish stings', included only seven trials involving 435 patients that met the inclusion criteria (Li et al, 2013). The authors concluded that the evidence from one study (on Physalia stings) suggested hot water immersion relieved pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(99,100) For pain relief, jellyfi sh sting should be treated with hot water immersion (45 o C or as hot as tolerable) for at least 20 minutes or for as long as the pain persists. (101)(102)(103)(104) (j) Dental injuries: Seek rapid medical consultation following tooth avulsion. Immediate re-implantation of an avulsed tooth within an hour provides the greatest chance of tooth survival.…”
Section: Medicalmentioning
confidence: 99%
“…Although, the evidence behind the currently suggested therapy is relatively weak [5,115]. The best preventive measure is to avoid any contact with seawater during the time jellyfish are invading.…”
Section: Treatment With Envenomationmentioning
confidence: 99%